ARTS PLAN: A Model Based System for Use in Planning a Performing Arts Series - Weinberg, Charles B; Shachmut, Kenneth M (Management science, 1978)
This paper is concerned with the application of marketing and management science to some of the problems involved in managing a series of performing arts presentations. Although some of the decisions are largely "artistic" and not subject to formal analytic procedures, many other decisions can be aided by model-based procedures. This paper describes some of the analytic procedures which are being used by the management of one performing arts series. The starting point for ARTS PLAN is dummy variable regression analysis of historical data which leads to a prediction of attendance at future performances. This prediction can be overridden by the manager if he or she disagrees with the forecast The forecast is then embedded in an interactive model which can be used for planning a season or for deciding which events to promote in a season already planned.